Deciphering the link: ferroptosis and its role in glioma - Wang, He; Liu, Yingfeng; Che, Shusheng; Li, Xiangjun; Tang, Dongxue; Lv, Shaojing; Zhao, Hai (Frontiers in Immunology, 2024)
Glioma, as the most frequently occurring primary malignancy in the central nervous system, significantly impacts patients' quality of life and cognitive abilities. Ferroptosis, a newly discovered form of cell death, is characterized by significant iron accumulation and lipid peroxidation. This process is fundamentally dependent on iron. Various factors inducing ferroptosis can either directly or indirectly influence glutathione peroxidase, leading to reduced antioxidant capabilities and an increase in lipid reactive oxygen species (ROS) within cells, culminating in oxidative cell death. Recent research indicates a strong connection between ferroptosis and a range of pathophysiological conditions, including tumors, neurological disorders, ischemia-reperfusion injuries, kidney damage, and hematological diseases. The regulation of ferroptosis to intervene in the progression of these diseases has emerged as a major area of interest in etiological research and therapy. However, the exact functional alterations and molecular mechanisms underlying ferroptosis remain to be extensively studied. The review firstly explores the intricate relationship between ferroptosis and glioma, highlighting how ferroptosis contributes to glioma pathogenesis and how glioma cells may resist this form of cell death. Then, we discuss recent studies that have identified potential ferroptosis inducers and inhibitors, which could serve as novel therapeutic strategies for glioma. We also examine the current challenges in targeting ferroptosis in glioma treatment, including the complexity of its regulation and the need for precise delivery methods. This review aims to provide a comprehensive overview of the current state of research on ferroptosis in glioma, offering insights into future therapeutic strategies and the broader implications of this novel cell death pathway in cancer biology.